2011
DOI: 10.3892/etm.2011.273
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive value of CEA and CYFRA 21-1 levels in advanced non-small cell lung cancer patients treated with gefitinib or erlotinib

Abstract: Abstract. The prognostic and predictive value of pre-treatment serum levels of carcinoembryonic antigen (CEA) and cytokeratin-19 fragments (CYFRA 21-1) were assessed in advanced non-small cell lung cancer (NSCLC) patients treated with gefitinib or erlotinib. Pre-treatment CEA and CYFRA 21-1 levels were measured in 123 advanced NSCLC patients receiving gefitinib or erlotinib. High CEA levels (h-CEA) were significantly associated with females, patients with adenocarcinoma and non-smokers. Low CYFRA 21-1 levels (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…There has also been a report suggesting that serum CYFRA 21–1 levels might serve as a prognostic factor in patients with recurrent NSCLC receiving 3 rd -line or later gefitinib therapy [30]. Some studies have suggested the possible prognostic value of pretreatment serum CYFRA 21–1 values (PCV) in patients with surgically treated lung adenocarcinoma [31] and advanced NSCLC [32-34]. However, none of the studies suggesting serum CYFRA 21–1 as a prognostic factor in patients with untreated advanced lung adenocarcinoma has included the EGFR mutation status as a variable.…”
Section: Introductionmentioning
confidence: 99%
“…There has also been a report suggesting that serum CYFRA 21–1 levels might serve as a prognostic factor in patients with recurrent NSCLC receiving 3 rd -line or later gefitinib therapy [30]. Some studies have suggested the possible prognostic value of pretreatment serum CYFRA 21–1 values (PCV) in patients with surgically treated lung adenocarcinoma [31] and advanced NSCLC [32-34]. However, none of the studies suggesting serum CYFRA 21–1 as a prognostic factor in patients with untreated advanced lung adenocarcinoma has included the EGFR mutation status as a variable.…”
Section: Introductionmentioning
confidence: 99%
“…CK19 has been reported to be over-expressed in many lung cancer tissue specimens (11,12), which results in an increase of the plasma CYFRA21-1 values (13). Some studies reported that CYFRA21-1 can be useful for pathological typing and assessment of treatment efficacy of NSCLC (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…10 It is estimated that 8-15% of patients with lung cancer have MPE, with higher frequencies observed in those with lung adenocarcinoma, 11 but the mechanism and genetic or epigenetic changes involved in MPE formation are not well understood.…”
Section: Introductionmentioning
confidence: 99%